Trains : a memoir of a hidden childhood during and after World War II - Winter, Miriam, 1933-2014. (Jackson, Mich. : Kelton Press, 1997)
Memoirs of a Jew born in Łódź in 1933. At the beginning of the war her family fled to Warsaw; in summer 1941 they left the ghetto and went to Ozarow. In November 1941 Winter's parents gave her to a Jewish woman who lived with false documents on the "Aryan side" of Warsaw; she passed the child on to Maria (Maryla) Oraczowa, a Polish woman whom they met on a train. Maryla took her to her home in Lvov, but Winter was soon recognized as a Jew and Maryla arranged other hiding places. Winter's life in hiding was a painful process of changing identity; she became a sincere Catholic in 1943 and an agnostic after the war. She remained with Maryla and her family, even though she was treated like a servant. Finally, she went away to school, married, and in 1969 emigrated to the USA. Her parents and brother perished in the Holocaust.
Keywords: Winter, Miriam, -- 1933-2014.; Holocaust, Jewish (1939-1945) -- Poland -- Personal narratives; Jewish children in the Holocaust -- Poland; Holocaust survivors -- Poland -- Biography